A Rapid and Sensitive UHPLC-MS/MS Method for Determination of 2, 3, 8-Trimethylellagic, a Potent Active Compound from Sanguisorba officinalis L., and Its Application in the Pharmacokinetic Study within Thrombocytopenia Rats. (16th December 2021) - Wang, Yuqing; Wu, Jianming; Li, Yunxia; Yang, Jing; Wang, Long; Wu, Anguo; Huang, Feihong; Jiang, Nan; Tang, Can; Li, Yan
Abstract : To investigate the pharmacokinetics of 2, 3, 8-trimethylellagic (TMEA) in rats in vivo and determine the possible effects of the pathological conditions and compatibility, a rapid and sensitive ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method for quantitative determination was developed. TMEA and Artemetin (internal standard, IS) were separated on an Acquity Shim-pack GIST column with a total running time of 7 min using gradient elution at a flow rate of 0.3 mL/min. The intraday and interday relative standard deviations were <9.50%, and the relative error of accuracy was between −5.70% and 2.96%. The calibration curve of TMEA demonstrated good linearity with r 2  = 0.9996, with the average recovery changing from 94.77% to 102.47% and the matrix effect from 93.16% to 100.15%. Compared with the normal group, the area under the plasma concentration-time curve from time 0 to the last time of quantifiable concentration (AUC(0 −  t ) ), area under the plasma concentration-time curve from time 0 extrapolated to infinite time (AUC(0 − ∞) ), and the maximum concentration ( C max ) of TMEA increased, whereas the time of maximum concentration ( T max ) and apparent clearance (CL/F) remarkably decreased in the TMEA group. With significantly reduced CL/F, AUC(0 −  t ), AUC(0 − ∞), and C max for TMEA were increased approximately one time after combining with 3, 7-Di-O-methylducheside A (DOMA). AUC(0 −  t ) and C max for TMEA in the 2, 3, 8-trimethylellagic-3, 8-dimethoxyellagic acid-2-oxyglucoside (TMEA-DMAG) group were significantly lower than that in the TMEA group with clearly prolonged T max and increased CL/F. These findings indicate that the changes in the pharmacokinetic parameters of TMEA may be caused by pathological and combination conditions.